Understanding the link between the Productive Safety Net Program and agrobiodiversity cultivation in Ethiopia - Gotor, Elisabetta; Kozicka, Marta; Pagnani, Tiziana; Occelli, Martina; Caracciolo, Francesco (2021)
Our study aimed at investigating the possible linkages between agrobiodiversity and the Ethiopian Productive Safety Net Program (PSNP), an extensive social protection program, which is part of Ethiopia’s national Food Security Program. Both agrobiodiversity and the PSNP have proven to be two critical elements helping to foster the resilience of smallholder farmers to climate-induced challenges. Surprisingly, there is still little evidence on the relationship between social protection programs and crop diversification. Thus, the potential relations of PSNP with farm-level diversification need further examination.